Life after Lisbon : Europe's Challenges to Promote Labour Force Participation and Reduce Income Inequality. - Stolk, Christian van (RAND Corp., 2011)
The economic crisis of 2008 has undone much of the progress on improving employment and growth in Europe. The review concludes that policy makers should focus on enabling social policy that allows individuals to achieve their productive potential.